STUDY OF THE DYNAMIC OF HELICOBACTER PYLORI INFECTION PREVALENCE IN DIFFERENT AGE GROUPS OF ST. PETERSBURG POPULATION IN 2007-2011 - A. V. Svarval (Sankt-Peterburg : NIIÈM imeni Pastera, 2014)
Abstract. Presence of specific antibodies to H. pylori and to its Cag A toxin was studied in 1917 persons, including 860 children and 1057 adults, in Pasteur Research Institute of Epidemiology and Microbiology, St. Petersburg, Russia. The studied group was presented by the subjectively healthy individuals and blood donors living in St. Petersburg. The growth and stabilization of serological positive rates to H. pilory at high level, as well as increasing the proportion of CagA-positive infection among children and adults in St. Petersburg in 2007–2011 have been established. There are 3 age risk groups of H. pylori infection among children population: 4–5 years, 7–8 years and 14–15 years. The shift of the maximum H. pylori seropositivity rates from age group of 30–39 years in 2007 to age group 40–49 years in 2011 was detected.